"The Lady in Pink: Dress and the Enigma of Gendered Space in Marcel Proust's Fiction" - Eva Maria Stadler (Studies in 20th & 21st Century Literature, 2005)
A study of the role of clothing as central to issues of characterization, description and historical reference in Marcel Proust's A la recherche du temps perdu. Focus on Odette de Crécy, one of the central characters in the novel, a courtesan who becomes the wife of Charles Swann but who first captivates the narrator's imagination when, as a child, he briefly sees her as a "Lady in Pink." Odette's role as a fashionable woman, as one of the best-dressed women in Parisian society, gives unity to her character. The description of her clothing, however, not only provides the occasion for an accurate recreation of contemporary dress codes. The links between clothing and a woman's body are explicitly explored in creating the character of Odette. Her femininity is defined specifically in terms of surfaces and objects and her personality seems to assume its reality from costume. Dress not only encloses her lovely appearance; it gives substance to her person and order to her life. Through the agency of dress this ordinary, even vulgar woman rises above her condition and enters a world of passion and poetry.
Keywords: clothing; characterization; description; historical reference; Marcel Proust; A la recherche du temps perdu; Odette de Crécy; Odette; courtesan; wife; Charles Swann; Lady in Pink; Pink; fashionable woman; Parisian society; clothes; dress codes; femininity; woman' s body; costume; surfaces; objects; appearance; agency of dress; women; body; dress; attire; define